Alloy design strategies to increase strength and its trade-offs together. (April 2021) - Han, Seung Zeon; Choi, Eun-Ae; Lim, Sung Hwan; Kim, Sangshik; Lee, Jehyun
Abstract: It is an ultimate goal for almost all the metallurgists to improve strength, ductility, formability and conductivity of metal together. However, ductility, formability and conductivity are generally known as the trade-offs for the increase in strength. It is because the mechanism(s) to increase the strength of metal is subject to be either harmful or irrelevant to those related to the trade-offs. A variety of metallurgical methods for improving both strength and trade-offs have been exploited through the morphological control of microstructure. This article addresses the microstructural aspects of strengthening a metal together with improving its trade-off properties of ductility, formability and conductivity. Particular emphasis was placed on the alloy design to control the interface energy between 2nd phases and alloy matrix. The reduction of interfacial energy between second phase and matrix can, for example, induce the uniform dispersion of ultra-fine second phase in a matrix, thereby increasing strength, conductivity and ductility simultaneously. The utilization of mechanically detrimental discontinuous precipitation is described as a method of improving the strength, ductility and conductivity of precipitation hardened alloys.